Arbuscular mycorrhizal fungus communities and their response to soil phosphorous differ between wild and domesticated enset (Ensete ventricosum) in Southern Ethiopia - Garo, G.; Geel, M. van; Eshetu, F.; Swennen, Rony L.; Honnay, O.; Vancampenhout, Karen (Elsevier, 2021)
We tested whether roots from indigenous wild enset in Southern Ethiopia harboured a more diverse and different AMF community compared to cultivated enset. Illumina MiSeq amplicon sequencing showed that AMF communities in both cultivated and wild enset were dominated by Glomeraceae which accounted for 64% of the 145 OTUs recorded. The majority of rare AMF OTUs occurred in cultivated enset, whereas Paraglomeraceae predominated in wild enset roots. AMF richness and diversity were lower in cultivated enset. AMF richness and diversity both in wild and cultivated enset were negatively influenced by available soil P, yet the effect was stronger in communities associated with wild enset. Our results suggest that enset domestication decreased the ability of the crop to associate with a more diverse community of AMF, supporting previous suggestions in other crops regarding reduced AMF diversity.